MYC-Nonamplified Secondary Lymphatic-Type Angiosarcoma With Prominent Lymphocytic Infiltrate Following Radiation Therapy for Myxoid Liposarcoma. (27th December 2022) - Krajisnik, Andrea; Balzer, Bonnie L.; Vail, Eric; Brien, Earl; Shon, Wonwoo
Abstract: Cutaneous angiosarcomas (AS) are uncommon and morphologically heterogeneous. Recently, a distinctive lymphatic-type AS with prominent lymphocytic infiltrate has been observed. Although conventional AS typically bear poor prognosis, lymphatic-type AS with prominent lymphocytic infiltrate and pseudolymphomatous AS show prolonged survival with rare extracutaneous spread. We describe a unique case of AS in a 55-year-old woman who received surgical resection and radiation therapy for her prior myxoid liposarcoma. She developed a suspected recurrence 15 years later. Microscopically, the lesion showed an infiltration of the reticular dermis by irregular interanastamosing vascular spaces lined by atypical endothelial cells with nuclear "hobnailing" and hyperchromasia. A prominent intratumoral and peritumoral lymphocytic infiltrate obscuring the tumor cells was also present. The tumor cells were diffusely positive for endothelial cell markers, including D2-40. Notably, there was no evidence of MYC gene amplification by FISH. Additional NGS-based molecular analysis demonstrated no significant genetic mutations. The patient is alive with a history of two local recurrences, but no evidence of metastasis. We present this case to raise awareness of MYC -nonamplified secondary lymphatic-type AS with prominent lymphocytic infiltrate (pseudolymphomatous AS) and to discuss its differential diagnosis.